Painting of Living Creatures from an Islamic and Western Perspective - Shaila Radhiyya Haqi; Nur Izzah Sofiyani; Shabrina Jauharotus Sakia; Pena Revisa Yahya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Painting of living creatures is a form of artistic expression that reflects the cultural views and values ​​of the society that created it. This journal aims to explore the differences in views between Islamic and Western traditions regarding the painting of living creatures, and the impact of these differences on the development of art. In the Islamic context, the depiction of living creatures is considered taboo based on the hadith that prohibits imitation of God's creation, so Islamic art places more emphasis on calligraphy, geometry, and non-figurative motifs. In contrast, Western painting, especially since the Renaissance era, shows freedom in depicting humans and nature with a realistic approach, as done by famous artists such as Leonardo da Vinci and Michelangelo. This study aims to analyze the fundamental differences in worldview, theology, and aesthetics between the two artistic traditions. Using a cross-cultural comparative approach, this study fills a gap in the study of painting of living creatures that has not been widely discussed in the modern context. Data were obtained through a literature review that included artworks, historical documents, and analysis of religious texts and theories. This type of research is qualitative research with a comparative approach, which focuses on a comparative analysis between two different artistic traditions in the context of the representation of living creatures.